Pendekatan Wasatiyah dalam Wacana Ayat-ayat Mutashābihāt: Analisis Terhadap Karya-karya Tafsir Nusantara Terpilih: The Moderation (Wasatiyyah) Approach in the Discourse of Mutashabihat Verses: An Analysis of Selected Exegesis Books in Malay Archipelago - Norasid, Muhamad Alihanafiah; Amir, Selamat; Yahya, Muhammad Arif (Jurnal Usuluddin, 2021)
The polemics of the Islamic schools of thought are often due to the understanding of the verses of mutashābihāt. In order to resolve the polemic, the wasatiyah approach in interacting with these kind of verses needs to be presented according to the framework of Ahl al-Sunnah wa al-Jama’ah. The attitude of not being too liberal and not literal (lā ifrāṭ wa lā tafrīṭ) is used as a guide in the effort to build unity, global stability and peace among the Islamic ummah. Therefore, this article aimed to highlight the wasatiyyah framework in the discourse of mutashābihāt verses towards realizing the unity of Muslims according to Ahl al-Sunnah wa al-Jama’ah’s beliefs. Efforts to harmonize the views between the two ideological mainstreams (salaf and khalaf) are highlighted by analyzing the interpretation of the verses of mutashābihāt in several selected works of tafsir in Malay Archipelago, namely Tafsir Nur al-Ihsan, Tafsir al-Qur’an Majid al-Nuur, Tafsir ‘Abr al-Athir, and Tafsir al-Azhar, using descriptive, text analysis and comparative methods. The results showed that the scholars’ interpretations in Malay Archipelago are open and moderated in the discourse of mutashābihāt verses. Therofore, The wasatiyyah approach displayed by them should be emulated to unify the Muslims’ comunities and firm on a peaceful beliefs.